The IoT and Cloud Technologies Based Smart Farming and its Applications - Mahalakshmi, P; Umamaheswari, S (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, people doing agriculture are gradually decreasing in all over the world. When agriculture turned out to be smart, people can get better result than traditional technologies followed early. Farmers using modern technologies can control their cost, maintenance and monitoring performance of their filed. IoT and cloud can be combined together and can be applied in various domains of agriculture like temperature detection, moisture sensing, controlling and monitoring irrigation and so on. Traditional methods of farming have lot of drawbacks like wasting of water resources, unaware of seeds sowing, etc. Precision agriculture can give more accurate and better result with modern technologies. In this paper, we presented some typical applications of IoT and Cloud in agriculture field and Security threads that causes obstacles in implementation of smart farming. This survey helps for the better understanding of different technologies and to build sustainable smart agriculture